Towards Smart Village : Rides Management Mobile Application As Tourism Digital Promotion And Marketing in Society 5.0 Era - Hartatik Hartatik; Nurul Firdaus; Abdul Aziz (International Journal of Artificial Intelligence Research, 2022)
In the context of developing tourism in various regions in Indonesia, many areas are developing the potential around them to be used as tourist attractions that can attract visitors or what are then referred to as "tourist villages." In its introduction, tourist villages also need promotion through digital media. One of the efforts to market to the wider community and make it easier for people who want to visit tourist villages to purchase entrance tickets for rides and find out information about what types of rides are available. By using the Agile-Scrum development method, it is possible to produce a product Implementation of the Tourism Village Mobile Application for the Ticket Management and Tourism Rides Management Module, in the form of an application where visitors can purchase tickets and tour packages through the tourist village application on their smartphone. The application does not only sell entry tickets but also sells ride tickets available in the tourist village